FOCAD Indel in a Family With Juvenile Polyposis Syndrome. Issue 1 (17th June 2022) - MacFarland, Suzanne P.; Xie, Hongbo; Dent, Maiah H.; Greed, Bridgid; Plon, Sharon E.; Scollon, Sarah R.; Brodeur, Garrett M.; Howe, James R.
Abstract : Juvenile polyposis syndrome (JPS) is a childhood polyposis syndrome with up to a 50% lifetime risk of gastrointestinal cancer. Germline pathogenic variants in BMPR1A and SMAD4 are responsible for around 40% of cases of JPS, but for the majority of individuals, the underlying genetic cause is unknown. We identified a family for which polyposis spanned four generations, and the proband had a clinical diagnosis of JPS. Next-generation sequencing was conducted, followed by Sanger sequencing confirmation. We identified an internal deletion of the FOCAD gene in all family members tested that altered the reading frame and is predicted to be pathogenic. We conclude that inactivation of the FOCAD gene is likely to cause JPS in this family.